Clinical and Analytical Evaluation of the Alinity m HR HPV Assay within the VALGENT-3 Framework - Dhillon, Sharonjit K.; Oštrbenk Valenčak, Anja; Xu, Lan; Poljak, Mario; Arbyn, Marc (Journal of clinical microbiology, 2021)
Only clinically validated human papillomavirus (HPV) tests should be used in cervical cancer screening. VALGENT provides a framework to validate new HPV tests. Only clinically validated human papillomavirus (HPV) tests should be used in cervical cancer screening. VALGENT provides a framework to validate new HPV tests. In the VALGENT-3 study, the clinical accuracy of the recently launched Abbott Alinity m HR HPV assay (Alinity m) to detect cervical precancerous lesions was assessed against the standard comparator test (Hybrid Capture 2; HC2) and against two previously validated alternative comparator tests (Abbott RealTi m e HR HPV and Roche cobas 4800 assays). Validation was conducted using 1,300 consecutive cervical samples from women attending an organized population-based cervical screening program enriched with 300 cytologically abnormal samples. Overall high-risk HPV test concordance was assessed by kappa values; the concordance for HPV-16 and HPV-18 was assessed for Alinity m, RealTi m e, and cobas, and the Linear Array (Roche) was used for more detailed genotyping concordance. In the total study population, the relative sensitivity and specificity for cervical intraepithelial neoplasia grade 2 or worse (CIN2+) and CIN3+ of Alinity m compared to HC2 was 1.02 (95% confidence interval [CI], 0.99 to 1.06) and 1.03 (95% CI, 0.99 to 1.06), respectively. The relative specificity for nondiseased subjects (≤CIN1) was 1.01 (95% CI, 1.00 to 1.02) (all p non-inferiority ≤ 0.001). Alinity m showed noninferior clinical accuracy among women 30 years or older when cobas or RealTi m e was used as a comparator. HPV genotype-specific concordance between Alinity m and the three comparator tests showed excellent agreement, with kappa values ranging from 0.82 to 1.00. In conclusion, Alinity m fulfills the international accuracy requirements for use in cervical cancer screening and shows excellent HPV genotype-specific concordance with three clinically validated HPV tests.